The dacian religious prohibition on consumption of wine. Perspectives on their alleged moral superiority in the Romanian historiography - Carbó García, Juan Ramón (ARYS. Antigüedad: Religiones y Sociedades, 2020)
Begining with the scarce ancient literary evidence about the Dacian religion, an idealized image of this people was subsequently developed, mainly because of the characteristics of a supposed religious reform developed in the first century BC, which would have included the prohibition on wine consumption. Analyzing that evidence, we shall raise the resulting perspectives defended by Romanian historiography of Dacianist type. Then we will try to compare the data offered by the literary sources with the latest archaeological evidence.
Keywords: Religious prohibitions; wine; Dacians; historiography; Dacia